2014
DOI: 10.1371/journal.pone.0087429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Genetic Diversity of Castanopsis (Fagaceae), the Dominant Tree Species in Japanese Broadleaved Evergreen Forests, Revealed by Analysis of EST-Associated Microsatellites

Abstract: The broadleaved evergreen forests of the East Asian warm temperate zone are characterised by their high biodiversity and endemism, and there is therefore a need to extend our understanding of its genetic diversity and phylogeographic patterns. Castanopsis (Fagaceae) is one of the dominant tree species in the broadleaved evergreen forests of Japan. In this study we investigate the genetic diversity, genetic structure and leaf epidermal morphology of 63 natural populations of C. sieboldii and C. cuspidata, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
3
41
0
1
Order By: Relevance
“…The relationship between acorn weevils and their host plants represents such an example. The distribution ranges and the population genetic structures of the acorn weevils (Coleoptera: Curculionidae), Curculio sikkimensis (Heller, 1927) and Curculio hilgendorfi (Harold, 1878), correspond very well with those of their laurel host plants, Castanopsis sieboldii and Castanopsis cuspidate , respectively (Aoki et al , , ). Modeling suggests that they were forced to the south and contracted their distribution ranges during glacial periods, but that they were forced to the north and expanded their distribution ranges during interglacial periods.…”
Section: Mechanisms For Establishment Of Insect Diversity In Japanmentioning
confidence: 97%
See 1 more Smart Citation
“…The relationship between acorn weevils and their host plants represents such an example. The distribution ranges and the population genetic structures of the acorn weevils (Coleoptera: Curculionidae), Curculio sikkimensis (Heller, 1927) and Curculio hilgendorfi (Harold, 1878), correspond very well with those of their laurel host plants, Castanopsis sieboldii and Castanopsis cuspidate , respectively (Aoki et al , , ). Modeling suggests that they were forced to the south and contracted their distribution ranges during glacial periods, but that they were forced to the north and expanded their distribution ranges during interglacial periods.…”
Section: Mechanisms For Establishment Of Insect Diversity In Japanmentioning
confidence: 97%
“…Such a high species diversity of Japanese plants, as well as the insect diversity, should be owed to various physical factors of location, climate, geography and geology of the Japanese Islands (Kubota et al ). In addition, insect‐plant coevolution would have enhanced speciation in some insect groups (Toju ; Azuma et al ; Aoki et al , ; Kusumi et al ).…”
Section: Mechanisms For Establishment Of Insect Diversity In Japanmentioning
confidence: 99%
“…Previous studies have shown that endemic species and species with narrow distribu-tion usually show lower levels of genetic diversity than widespread species (Tanahara and Maki, 2010;Chen et al, 2013;Duan et al, 2013;Nguyen et al, 2013;Aoki et al, 2014). However, C. arborescens was found to possess an unexpectedly high rate of genetic diversity (Table 3), indicating the species ability to adapt to varying environmental conditions.…”
Section: Genetic Diversitymentioning
confidence: 86%
“…et Mashiba (Fagaceae). We chose C. sieboldii as the focal host species because this species is widely distributed across different climate regions of the Japanese archipelago and its phylogeographic pattern over its distribution range has been already documented with genetic markers (Aoki et al , 2014). Importantly, unlike Europe and North America, ice sheets were not present in the Japanese archipelago during the Quaternary period, and this, together with the complex mountainous terrain of Japan, resulted in the establishment of tree refugia in multiple regions across Japan (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Tsukada, 1984). Therefore, the present distributions of individual genotypes of single species are assumed to reflect the environmental gradients like climate (Tsukada, 1984; Aoki et al , 2014). For these features, we considered C. sieboldii in Japan as the appropriate host species to evaluate the effect of host genotypes and genotypic diversity on the geographic distribution of the associated ECM fungal community.…”
Section: Introductionmentioning
confidence: 99%